WHEN LOW CLASS CONFRONTS HIGH CLASS: AN ANALYSIS OF ‘PETRUK’ INTERPERSONAL MEANING THROUGH HIS SPEECH FUNCTIONS IN JAVANESE PERFORMING ART ‘KETHOPRAK’ - Nafisa Ghanima Shanty (Master Program in Linguistics, Diponegoro University, 2014)
How low class confronts high class people could be shown from conversation exchanges that occur. This study is aimed at analyzing Petruk’s speeches—as low class person in Kethoprak performance, who confronts the high class—King of Astina. The data were analyzed using Halliday’s Systemic Functional Grammar, dealing with ‘responding speech function’ and ‘typical moods’ in the speech function. Petruk mostly used humilific ‘Ngoko’ style in most of his exchanges with 13 confrontations, 12 supports, and 2 initiations. He also used declarative and interrogative moods to confront. The study proves that Kethoprak is a reflection of low class victory. Bagaimana kelas bawah dan kelas atas berkonfrontasi terlihat saat perpindahan dialog terjadi. Penelitian ini mengkaji ujaran Petruk dalam pertunjukkan Kethoprak, sebagai bentuk perlawanan kelas bawah terhadap kelas atas—yaitu Raja Astina. Data dikaji menggunakan pendekatan Tata Bahasa Fungsional Sistemik dari Halliday. Fokus kajian adalah pada fungsi respon dan jenis-jenis Mood (mode) dalam ujaran Petruk. Petruk banyak menggunakan gaya bahasa Ngoko dalam dialog, 13 kali sikap berkonfrontasi, 12 kali mendukung dan 2 kali sikap memulai dalam dialog. Petruk menggunakan mode deklarasi dan bertanya pada saat berkonfrontasi. Hal ini menunjukkan bahwa Kethoprak merupakan sebuah refleksi kemenangan kelas bawah.